Mitigating vehicular emissions in Kathmandu valley by a clean energy approach - Chaulagain, Pitambar; Lamichhane, Binaya Kumar; Pradhan, Rush; Bhusal, Gyan Prasad; Bhandari, Kedar Prasad; Parajuli, Bishworam (Journal of Innovations in Engineering Education, 2025)
The Kathmandu Valley has experienced a sharp decline in air quality over the last few decades, primarily due to a surge in vehicular emissions driven by rapid and unmanaged urbanization. This study aimed to quantify the annual emissions from the vehicular sector and assess the potential reductions achievable through the electrification of public buses. A bottom-up approach was employed, incorporating real-time traffic data, structured surveys, and localized emission factors to quantify the total vehicular emissions. Approximately 1235 kilotons of GHGs and 85 kilotons of ambient air pollutants were estimated annually. Public buses, although comprising only 6% of the vehicle fleet, contributed nearly half of the total GHG emissions due to their use of diesel fuel, longer travel distances, and low fuel economy. The study presents the first scenario-based replacement analysis conducted in the context of Kathmandu. The results demonstrate that replacing 100% of diesel buses with electric alternatives could reduce GHG emissions by 49% and air pollutants by 17%. Additionally, a review of national and local policies highlights ambitious but under-implemented targets for transport electrification. The study provides valuable insights for emission mitigation through targeted electrification, emphasizing the need for infrastructure, incentives, and coordinated policy support at both the national and local levels to realize sustainable urban mobility in Nepal.